A velocity corrected unresolved CFD-DEM coupled method to reproduce wake effects at moderate Reynolds number. Issue 8 (26th June 2019) - Wang, Zekun; Walayat, Khuram; Liu, Moubin
Abstract : Purpose: The purpose of this paper is to develop a corrected unresolved CFD-DEM method that can reproduce the wake effects in modeling particulate flows at moderate Reynolds number. Design/methodology/approach: First, the velocity field in the wake behind a settling particle is numerically investigated by a resolved method, in which the finite volume method (FVM) is applied to model the fluid flow, discrete element method (DEM) is applied to simulate the motion of particles and immersed boundary method (IBM) is used to tackle fluid solid interaction. Second, an analytical scaling law is given, which can effectively describe the velocity field in the wake behind the settling particle at low and middle Reynolds numbers. Third, this analytical expression is incorporated into unresolved modeling to correct the relative velocity between the particle and its surrounding fluid and enable the influence of the wake of the particle on its neighboring particles. Findings: Two numerical examples, the sedimentation of dual particles, a list of particles and even more particles are provided to show the effectiveness of the presented velocity corrected unresolved method (VCUM). It is found that, in both examples simulated with VCUM, the relative positions of the particles changed, and drafting & kissing phenomenon and particle clustering phenomenon were clearly observed. Practical implications: The developed VCUM can be highly beneficial for modeling industrial particulate flows with DKT and particle clustering phenomena. Originality/value: VCUM innovatively incorporates the wake effects into unresolved CFD-DEM method. It improves the computational accuracy of conventional unresolved methods with comparable results from resolved modeling, while the computational cost is greatly reduced.